Pengaruh Kualitas Pelayanan dan Harga terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan sebagai Variabel Intervening (Studi Kasus Pada RM Ayam Goreng Bu Bengat) - Jihan Mirta Puasantika; Bulan Prabawani (Universitas Diponegoro, 2018)
RM Ayam Goreng Bu Bengat is one of the famous restaurants in the north coast area of Batang - Semarang, precisely located at Jl. Raya Kutosari-Gringsing, Batang Regency. The restaurant which has been established since 1952 is currently facing competition, so it needs to pay attention to and maintain the quality of service to provide satisfaction and create customer loyalty. In addition, currently it is threatened to be affected by the construction of the Batang – Semarang toll road. This study aims to determine the effect of service quality and price on customer loyalty through customer satisfaction of RM Ayam Goreng Bu Bengat. The type of research used is explanatory research. Data collection techniques used are using questionnaire tools, with samples used by 100 people using accidental techniques and purposive sampling. Data were analyzed through cross tabulation test, correlation test, determination test, simple linear regression test, multiple linear regression test, significance test (t test and F test), sobel test with the help of IBM SPSS (Statistical Product and Service Solution) version 16.0. The results showed that the variable customer satisfaction is a partial mediation variable that is able to mediate the effect of service quality and price on customer loyalty because the output of the single test is greater than t table. Based on the results of the study, researchers suggested that RM Ayam Goreng Bu Bengat need to realize the expectations of customers more, especially in terms of price and service quality to increase customer satisfaction and customer loyalty.